Community Cultural Wealth and Science, Technology, Engineering, and Mathematics (STEM) Identities as Motivators for Black Boys to Participate in a High School Academy of Engineering - Edward C. Fletcher Jr; Turhan K. Carroll (MDPI AG, 2024)
Researchers have emphasized how the high school STEM-themed career academy model benefits ethnically and racially diverse learners by promoting positive STEM identities and raising the interest of students to pursue STEM college and career pathways. The purpose of this study was to examine the reasons why Black boys participated in a high school academy of engineering. We were also interested in identifying academy features that helped promote (or inhibit) positive STEM identities among Black male students. In this qualitative study, we used data from 17 Black male high school academy of engineering students. We analyzed the interview transcripts using a constant comparative method. Using an embedded case study approach, we compared our findings to the community cultural wealth (CCW) factors and the factors that researchers have found to influence students' STEM identities. We found that the participants brought six forms of capital with them that served as sources of motivation to participate in the program. The forms of capital that were related to the CCW framework included aspirational, familial, navigational, resistance, and social. While we did not uncover linguistic capital in our data analysis, we did find an additional source of capital that was not reflected in the CCW framework. We found that the Black boys had natural STEM talent based on the formation of STEM identities. The students had high aptitudes in STEM-related subjects, and they were engaged by participating in hands-on activities. We recommend that schools integrate STEM curricula for Black boys and provide Black men to serve as STEM role models through guest speaking opportunities, job shadowing, mentoring, internships, and other work-based learning experiences.